BUKU TEKS AL-LUGHAH AL-‘ARABIYAH AL-MU’ĀSHIRAH BAGI PENUTUR NON ARAB Desain, Kontruksi dan Implementasi - Toni Pransiska (Program Pascasarjana Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
Textbook is one components that affects the achievement of learning goals, especially the Arabic text books. The book al-Lughah al-‘Arabiyah al-Mu’ashirah was written by Eckehard Schulz is one of the Arabic language textbooks that studied by the Arabic language learners. This Arabic textbook is an intensive basic course in Arabic language for beginners student at the Oriental Institute of the University of Leipzig Germany. This book aims to study Standar and Modern Arabic Language, both written and communication. Therefore, this article will describe about the contents and systematic book comprehensively. Beside that, this book will be analyzed more in depth with the design criteria ideal textbook development through several stages such as selection, gradation, presentation and repetition. finally, through it will be known aspects of important notes and excellences as a Arabic text book for non Arab.